Purification and Characterization of a Noble Thermostable Alpha-amylase from Anoxybacillus tengchongensis RA1-2-1 Isolated from Geothermal Spring of Nepal - Timilsina, Parash Mani; Pandey, Gyanu Raj; Shrestha, Asmita; Ojha, Manish; Baral, Garima; Karki, Tika Bahadur (Journal of Food Science and Technology Nepal, 2020)
A thermophilic amylolytic strain, Anoxybacillus tengchongensis RA1-2-1 was isolated from geothermal spring of Rasuwagadi district of Nepal. The BLAST alignment of the 16s rRNA sequence revealed 99.3% similarity with the type strain Anoxybacillus tengchongensis T-11. The morphological, physiological and biochemical properties were similar to the type strain. The enzyme from the strain was purified to 40-fold purification by DEAE-cellulose ion exchange chromatography. The Km value of the enzyme was 0.68±0.05 mg/ml. The optimum pH and temperature were 7.0 and 70 °C. SDS-PAGE analysis showed a single band at 69 kDa. The half-life of the enzyme at 70°C and 80°C were 85.01min and 51.96 min respectively. TLC analysis of the hydrolysis product showed that the enzyme is maltogenic amylase. The calcium independent enzyme was completely inhibited by Hg2+ but showed inhibitory effect in the range of 100 %-30 % in the presence of other salts at 1-10 mM concentrations.